The Harmony of Islam and Pancasila in Religious Discourse in Indonesia - Hidayatulloh, Taufik; Saumantri, Theguh (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2023)
Indonesia is a country with a majority of its population practicing Islam, but it does not claim itself as an Islamic state. The presence of Pancasila as a melting pot has led to the emergence of a highly elegant Civil Society in this nation. Islam and Pancasila, in principle, are aligned and harmonious within the context of Indonesian democracy. The purpose of this research focuses on the harmonization of Islam and Pancasila in the study of religious moderation in Indonesia. The study employs a qualitative approach through a literature review and field studies involving observations and documentation. The research findings explain that religion and Pancasila are in alignment, with religion serving as a way of life for its followers, while Pancasila represents the way of life for the religiously diverse Indonesian nation. In the literature on religious moderation in Indonesia, religion must provide enlightenment to its adherents so that they can accept and appreciate the noble values of Pancasila. Conversely, the existence of Pancasila must also protect all religious communities, including those who do not adhere to any religion or hold different beliefs. This is why the actualization of religious moderation in society has become a distinctive characteristic of Indonesia, both socially and religiously.